The Endophytic Actinobacterial Toxicity Test of Ginger (Zingiber officinale Roscoe) Used The BSLT (Brine Shrimp Lethality Test) Method - Sri Rahayu; Lenni Fitri; Yulia Sari Ismail (Elkawnie: Journal of Islamic Science and Technology, 2021)
Abstract: Cancer is the biggest cause of death in Indonesia. Cancer treatment efforts have been made but it could harm cancer patients. It is necessary to find another alternative from nature as an anticancer. This study aims to see the ability of endophytic actinobacterial isolates from ginger (Zingiber officinale) as an anticancer tested using the BSLT method (Brine Shrimp Lethality Test) by calculating the values of LC50 and LT50. The best value isolates from the BSLT method, then tested using phytochemical ethanol extract. The highest toxicity value was found in AJ2 isolates. LC50 and LT50 values of AJ2 isolates were 309.358 µg/ml and 11.879 hours. Phytochemical results of ethanol extract of AJ2 isolates were detected containing steroids, terpenoids, phenols, tannins, flavonoids, alkaloids, and saponins. AJ2 isolates which derived from ginger endophytic actinobacteria have potential as an anticancer because they have high toxic values that rised rapidly.Abstrak: Kanker menjadi penyebab kematian terbesar di Indonesia. Upaya pengobatan kanker sudah dilakukan namun memberikan dampak negatif bagi penderita kanker. Perlu dilakukan penemuan alternatif lain berasal dari alam sebagai antikanker. Penelitian ini bertujuan untuk melihat kemampuan isolat aktinobakteri endofit asal jahe (Zingiber officinale) sebagai antikanker. 7 isolat aktinobakteri endofit jahe diuji menggunakan metode BSLT (Brine Shrimp Lethality Test) dengan menghitung nilai LC50 dan LT50. Isolat nilai terbaik dari metode BSLT, selanjutnya diuji  menggunakan fitokimia ekstrak etanol. Nilai toksisitas tertinggi terdapat pada isolat AJ2. Nilai LC50 dan LT50 isolat AJ2 adalah 309,358 µg/ml dan 11,879 jam. Hasil fitokimia ekstrak etanol isolat AJ2 terdeteksi mengandung steroid, terpenoid, fenol, tanin, flavonoid, alkaloid dan saponin. Isolat AJ2 yang berasal dari actinobacteria endofit jahe berpotensi sebagai antikanker karena memiliki nilai toksik yang tinggi dalam waktu singkat.